Is quantitative coronary angiography reliable in assessing the lumen gain after treatment with the everolimus-eluting bioresorbable polylactide scaffold? - Sotomi Y. (2017)
© 2016 Europa Digital & Publishing. All rights reserved. Aims: The current study aimed to assess the difference in lumen dimension measurements between optical coherence tomography (OCT) and quantitative coronary angiography (QCA) in the polymeric bioresorbable scaffold and metallic stent. Methods and results: In the randomised ABSORB Japan trial, 87 lesions in the Absorb arm and 44 lesions in the XIENCE arm were analysed. Post-procedural OCT-QCA lumen dimensions were assessed in matched proximal/distal non-stented/non-scaffolded reference (n=199), scaffolded (n=145) and stented (n=75) cross-sections at the two device edges using the Bland-Altman method. In the non-stented/nonscaffolded reference segments, QCA systematically underestimated lumen diameter (LD) compared with OCT (accuracy,-0.26 mm; precision, 0.47 mm; 95% limits of agreement as a mean bias±1.96 standard deviation,-1.18-0.66 mm). When compared to OCT, QCA of the Absorb led to a more severe underestimation of the LD (-0.30 mm; 0.39 mm;-1.06-0.46 mm) than with the XIENCE (-0.14 mm; 0.31 mm;-0.75-0.46 mm). QCA underestimated LD by 9.1%, 4.9%, and 9.8% in the reference, stented, and scaffolded segments, respectively. The protrusion distance of struts was larger in the Absorb arm than in the XIENCE arm (135±27 μm vs. 18±26 μm, p < 0.001), and may have contributed to the observed differences. Conclusions: In-device QCA measurement was differently affected by the presence of a metallic or polymeric scaffold, a fact that had a significant impact on the QCA assessment of acute gain and post-procedural minimum LD.